Pensamientos sobre el otro 11 de septiembre en memoria de un futuro justo - Gregory Lobo (Revista de Estudios Sociales, 2004)
In this essay the author reflects on the 'capitalist miracle' that began in South America on September 11, 1973, when the Chilean military, directed by General Pinochet and with the support of the United States, bombed and destroyed Chilean democracy for having tried to freely construct socialism. It is argued that September 11 has to be seen as a key moment in a barbarous and mostly successful campaign against socialism, and since then it would seem to be over as a project. However, since the economic miracle continues in crisis and capitalism continues to deprive too many people of basic necessities, the article concludes with the proposition that our memory of the future be reanimated, the memory of a future in which there was no poverty, scarcity, or war